NASIONALISME DALAM TEROR DI MANDAR TAHUN 1947 - Hamid, Abd Rahman (Paramita: Historical Studies Journal, 2016)
The desire becoming the new state (Republic) had been paid expensively by Mandar people. In February 1947, Westerling commited massacre in Galung Lombok and the surrounding areas. The victims were accused of being extremists, robbers, and murderers. They are executed without process of law process and forgiveness. This incident became the historical milestone in the area in defending the Republic from terror of Dutch troops. The movement had influence and extensive network, not only in South Sulawesi, but also in Java and Kalimantan. Peopleâs struggles were organized by KRIS Muda and GAPRI5.3.1. As a results of this study, it was found that there was encounter between nationalism and religion. Other organizations, particularly ALRI-PS, had role for defending the Republic. Choosing Mandar as target location for Westerling terror showed an important and powerful influence of the movement struggle in this region.Â Keinginan menjadi negara baru (republik) telah dibayar mahal oleh rakyat Mandar. Pada bulan Februari 1947, pasukan Westerling melakukan pembantaian massal di Galung Lombok dan daerah sekitarnya. Para korban dituduh sebagai ekstrimis, perampok, dan pembunuh. Mereka dieksekusi mati tanpa proses hukum dan ampun. Peristiwa ini menjadi tonggak sejarah daerah ini dalam membela Republik dari teror pasukan Be-landa. Gerakan itu memiliki pengaruh dan jaringan yang luas, tidak hanya di Sulawesi Selatan, tetapi juga Jawa dan Kalimantan.Perjuangan rakyat terorganisasi lewat KRIS Muda dan GAPRI 5.3.1. Dari hasil studi ini ditemukan adanya perjumpaan antara nasionalisme dan agama. Organisasi lain, khususnya ALRI-PS, berperan dalam membela republik. Dipilihnya Mandar sebagai lokasi sasaran teror Westerling menunjukkan penting dan kuatnya gerakan pengaruh perjuangan dari daerah ini.Â